Application of rainbow refractometry for measurement of droplets with solid inclusions. (1st January 2018) - Li, Can; Wu, Xue-cheng; Cao, Jian-zheng; Chen, Ling-hong; Gréhan, Gerard; Cen, Ke-fa
Highlights: Application of rainbow refractometry for measurement of droplets with solid inclusions. A rainbow extinction model of a droplet with solid inclusions is deduced. Disturbances to rainbow signal caused by solid inclusions are analyzed. Solid Inclusions at low concentration have little effect on the GRT measurement. Extinction characteristics of rainbow peak are used to analyze solid concentration. Abstract: Characterization of droplets with solid inclusions is of great research interest and has wide industrial applications. Reported here is a theoretical and experimental investigation of the measurement of droplets with solid inclusions using rainbow refractometry. A rainbow extinction model of a droplet with solid inclusions was deduced based on Beer-Lambert's Law. It takes into account the volume concentration, relative size, scattering efficiency of the solid inclusion, and liquid refractive index. An acoustic levitation system for a single droplet and a global rainbow instrumentation system for spray were integrated to study the effect of the H2 O-CaCO3 suspension droplets on the rainbow signal and the measured parameters. The results showed that the rainbow encountered unusual disturbances, introduced by the solid inclusions, but its overall structure was not destroyed. Discoveries also included that for volume concentrations of 2.5% or less the CaCO3 particles with diameters below 4 μm had little effect on the measured parameters of the host droplet. The extinction characteristic was also analyzed. The rainbow extinction model failed to quantity the volume concentration of CaCO3, but succeeded in its qualitative analysis.